Bioclimatic classification of the Mexican Pacific slope and its relationship with potential vegetation - Macías Rodríguez, Miguel Ángel; Peinado Lorca, Manuel; Giménez de Azcárate, Joaquín; Aguirre Martínez, Juan Luis; Delgadillo Rodríguez, José (Instituto de Ecología, A.C., 2014)
In this study we address the relationship between climate and vegetation in the territory of the Mexican Pacific rim, a strip of 100 km wide that extends from the coast landwards with its north and south limits coinciding with Mexico’s border with the United States of America and Guatemala, respectively. Relationships were established from bioclimatic analysis performed with temperature and precipitation data from 691 weather stations existing in the study area. The bioclimatic diagnosis identified the Mediterranean and Tropical macrobioclimates, the Mediterranean Pluviseasonal Oceanic, Mediterranean Xeric Oceanic, Mediterranean Desert Oceanic, Mediterranean Hyperdesertic Oceanic, Tropical Pluvial, Tropical Pluviseasonal, Tropical Xeric, Tropical Desertic and Tropical Hiperdesertic bioclimates, and 30 isobioclimates. The field sampling was focused towards physiognomic and floristic characterization of the natural potential vegetation of the different bioclimatic units, thereby establishing the main diagnostic features (bio-indicators and physiognomic-structural elements) of the bioclimatic sequence along the latitudinal gradient.